Improve the Overall Performances of Lithium Ion Batteries by a Facile Method of Modifying the Surface of Cu Current Collector with Carbon. (10th September 2015) - Kang, Shu-Wen; Xie, Hai-Ming; Zhang, Weimin; Zhang, Jing-Ping; Ma, Zifeng; Wang, Rong-Shun; Wu, Xing-Long
Graphical abstract: Highlights: A facile and mass-producible strategy was developed to modify the surface of Cu foils with carbon. The modified carbon is robust and strong. Overall performances of lithium ion batteries were improved by the surface carbon modification on Cu current collector. Full-cell systems were used to evaluate the effects of Cu surface modification. ABSTRACT: We have developed a facile and mass-producible strategy named electric discharge method to successfully improve the surface properties of Cu foils with rough carbon layer. Electrochemical tests in half-cells demonstrate that the coated carbon layer can significantly reduce the polarization resistance and enhance the reversible capacity of graphite anode when utilizing the Cu foils as current collector for lithium ion batteries. More importantly, the developed carbon coated Cu anode current collector can also improve the overall performances of LiFePO4 full cells in terms of enhanced rate capability (from 887.9 to 946.3 mAh at 4C rate), reduced polarization voltage (11.7 mV lower at 4C rate), longer cycle life (about 650 increased cycles if taking 80 % capacity retention as the end of cycle life when used at 1 C rate) as well as improved low-temperature performance (capacity retention: 42.87% vs. 38.85% at -20 °C).